2020
DOI: 10.1371/journal.pone.0231387
|View full text |Cite
|
Sign up to set email alerts
|

Beware of vested interests: Epistemic vigilance improves reasoning about scientific evidence (for some people)

Abstract: In public disputes, stakeholders sometimes misrepresent statistics or other types of scientific evidence to support their claims. One of the reasons this is problematic is that citizens often do not have the motivation nor the cognitive skills to accurately judge the meaning of statistics and thus run the risk of being misinformed. This study reports an experiment investigating the conditions under which people become vigilant towards a source's claim and thus reason more carefully about the supporting evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…Individuals also take an expert's motives into account when evaluating trustworthiness; for example, readers were more inclined to trust a scientist when they believed the scientist intended to inform rather than persuade them , when the scientist provided a two-sided stance (instead of a one-sided stance) (Mayweg-Paus and Jucks, 2018) or mentioned the ethical aspects of a scientific issue (Hendriks et al, 2016). Furthermore, people perceived a source to be less trustworthy when the source had a vested interest in a claim (König and Jucks, 2019;Gierth and Bromme, 2020); this even sometimes motivated people to engage in effortful processing of complex evidence (Gierth and Bromme, 2020).…”
Section: Source Evaluationmentioning
confidence: 99%
“…Individuals also take an expert's motives into account when evaluating trustworthiness; for example, readers were more inclined to trust a scientist when they believed the scientist intended to inform rather than persuade them , when the scientist provided a two-sided stance (instead of a one-sided stance) (Mayweg-Paus and Jucks, 2018) or mentioned the ethical aspects of a scientific issue (Hendriks et al, 2016). Furthermore, people perceived a source to be less trustworthy when the source had a vested interest in a claim (König and Jucks, 2019;Gierth and Bromme, 2020); this even sometimes motivated people to engage in effortful processing of complex evidence (Gierth and Bromme, 2020).…”
Section: Source Evaluationmentioning
confidence: 99%
“…Disclosing such personal interest in a scientific endeavor might be able to bridge the stereotypical perception of cold and distant "science nerds" by revealing passionate, human and, thus, more relatable side of a researcher. When received negatively, however, "me-search" might be regarded as harboring vested interests, which casts doubts on a researcher's neutrality and objectivity [8][9][10][11]42].…”
Section: Plos Onementioning
confidence: 99%
“…Does that suggest that the general public tends to turn a blind eye on conflicts of interest that may arise from a researchers' personal affection by their research object? While the Jill Bolte Taylor case seems to suggest so, research on science communication and public understanding of science has shown that people are highly sensitive to potential conflicts of interest arising from researchers' personal involvement: perceiving researchers as pursuing an "agenda" for personal reasons is a major factor predicting people's loss of trust in researchers and science [8][9][10][11]. On the other hand, people may see personal ("autoethnographic") experiences of researchers personally affected by their topic as valuable and laudable -it may imply that "they know what they're talking about" [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Sperber et al (2010) describe epistemic vigilance as “not the opposite of trust; the opposite of blind trust (p. 235),” and they argue that trustful communication between individuals can only be possible if humans possess cognitive mechanisms to identify what is untrue. By doing so, individuals limit potential harm of relying on testimony without question (Gierth & Bromme, 2020). Epistemic vigilance can be achieved by “thinking slow” or thinking critically to assess a communicator's perceived competence and benevolence, and to evaluate the validity of claims and justifications (Kahneman, 2011; Sperber et al, 2010).…”
Section: Theoretical Framing and Relevant Literaturementioning
confidence: 99%